Réponses

2013-06-13T17:44:43+02:00

a) 3x+7=34

3x=34-7

3x=27

x=27/3

x=9

 

b) 2+4y=-6

4y=-6-2

4y=-8

y=8/-4

y=-2

 

c) -3-2a=7

-2a=7+3

-2a=10

a=10/-2

a= -5

 

d) -3=-3t-12

-3+12=-3t

9=-3t

9/-3=t

t=-3

 

Questions de raisonnement par mp ;)

2013-06-13T18:40:05+02:00
A) 3x+7=34        3*9+7=34

3x=34-7

x=27/3

x=9

 

b) 2+4y=-6     2+4*(-2)=-6

4y=-8

y=8/-4

y=-2

 

c) -3-2a=7    -3-2*(-5)=7

-2a=10

a=10/-2

a= -5

 

d) -3=-3t-12   -3*(-3)-12=-3

9=-3t

9/-3=t

t=-3

voilà les solutions testées et aprouvées